Size spectra and other size-related variables of river fish communities: systematic changes along the altitudinal gradient on pristine Andean streams - Benejam, Lluis (2018)
The estimation of biodiversity is complex in remote areas like Andean-Amazon piedmont where the lack of knowledge is noticeable and most species have not yet been identified. An alternative to the taxonomical approach to assess biodiversity and community structure is to study the body size structure of the community. The present study aimed to identify systematic changes of the size structure of fish communities along the altitudinal gradient of pristine Andean streams. At the same time, we assessed if size structure of fish communities could be an alternative or complementary approach to traditional taxonomic metrics of ecological assessment. This study was conducted along two rivers of eastern Andean piedmont: Hacha River and Alto Madre de Dios basin. Our analysis showed lower values of total size range, maximum length and number of size classes in the highest places and increasing in lower reaches of the rivers. Concerning abundance size spectra, we found flatter slopes (indicating higher relative abundance of large fish) and lower coefficient of determination (i.e. less linear size spectra) and intercept at y-axis on upstream reaches. On the other hand, fish abundance, species richness and species diversity increasing from upstream to downstream. These systematic changes on size-related variables were similar using both basins together or independently and may be used in future studies as management reference conditions when assessing the effect of perturbations in freshwater ecosystems, while bypassing the error associated with the lack of taxonomic information. © 2018 Elsevier Ltd